Mobility of Transgenic Nucleic Acids and Proteins within Grafted Rootstocks for Agricultural Improvement - Haroldsen, Victor; Szczerba, Mark W.; Aktas, Hakan; Lopez, Javier; Odias, Mar J.; Chi-Ham, Cecilia L.; Labavitch, John; Bennett, Alan B.; Powell, Ann L. (Frontiers in Plant Science, 2012)
Grafting has been used in agriculture for over two thousand years. With modern advances in biotechnology, new options for utilizing this proven horticultural technique are emerging. Specifically, trans-grafting, the combination of a genetically engineered (GE) rootstock with a wild-type (WT) scion, has the potential to provide biotic and abiotic stress tolerance or to increase plant vigor and productivity. Yet, it is unclear whether nucleic acids and proteins will be transmitted across a graft and, if so, whether this movement may affect the efficacy of the trans-grafting approach and/or regulatory oversight of the WT scion and its products. There are reports of the movement of organellar DNA and cellular mRNAs and proteins across graft unions, but to what extent these molecules affect performance of the scion is not clear. Strategies that can be used to limit or enhance nucleic acid or protein movement in order to maximize trans-grafting benefits have not been defined. This paper reviews, using specific examples, the transport of nucleic acids and proteins between rootstock and scion with the objectives of increasing the benefits grafting, particularly for pathogen resistance and defining how use of GE rootstocks effectively extends the horticultural utility of grafting.